Significant variation in mortality and functional outcome after acute ischaemic stroke between western countries: data from the tinzaparin in acute ischaemic stroke trial (TAIST). Issue 3 (26th July 2005) - Gray, L J; Sprigg, N; Bath, P M W; Sørensen, P; Lindenstrøm, E; Boysen, G; De Deyn, P P; Friis, P; Leys, D; Marttila, R; Olsson, J-E; O'Neill, D; et al.
Abstract : Background: The medical care of patients with acute stroke varies considerably between countries. This could lead to measurable differences in mortality and functional outcome. Objective: To compare case mix, clinical management, and functional outcome in stroke between 11 countries. Methods: All 1484 patients from 11 countries who were enrolled into the tinzaparin in acute ischaemic stroke trial (TAIST) were included in this substudy. Information collected prospectively on demographics, risk factors, clinical features, measures of service quality (for example, admission to a stroke unit), and outcome were assessed. Outcomes were adjusted for treatment assignment, case mix, and service relative to the British Isles. Results: Differences in case mix (mostly minor) and clinical service (many of prognostic relevance) were present between the countries. Significant differences in outcome were present between the countries. When assessed by geographical region, death or dependency were lower in North America (odds ratio (OR) adjusted for treatment group only = 0.52 (95% confidence interval, 0.39 to 0.71) and north west Europe (OR = 0.54 (0.37 to 0.78)) relative to the British Isles; similar reductions were found when adjustments were made for 11 case mix variables and five service quality measures. Similarly, case fatality rates were lower in North America (OR = 0.44 (0.30 to 0.66)) and Scandinavia (OR = 0.50 (0.33 to 0.74)) relative to the British Isles, whether crude or adjusted for case mix and service quality. Conclusions: Both functional outcome and case fatality vary considerably between countries, even when adjusted for prognostic case mix variables and measures of good stroke care. Differing health care systems and the management of patients with acute stroke may contribute to these findings.